2021
DOI: 10.1080/19336918.2021.1892397
|View full text |Cite
|
Sign up to set email alerts
|

The Netrin-1-Neogenin-1 signaling axis controls neuroblastoma cell migration via integrin-β1 and focal adhesion kinase activation

Abstract: Neuroblastoma is a highly metastatic tumor that emerges from neural crest cell progenitors. Focal Adhesion Kinase (FAK) is a regulator of cell migration that binds to the receptor Neogenin-1 and is upregulated in neuroblastoma. Here, we show that Netrin-1 ligand binding to Neogenin-1 leads to FAK autophosphorylation and integrin β1 activation in a FAK dependent manner, thus promoting neuroblastoma cell migration. Moreover, Neogenin-1, which was detected in all tumor stages and was required for neuroblastoma ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 55 publications
0
4
0
1
Order By: Relevance
“…NEO-1 is a transmembrane receptor that associates with Focal Adhesion Kinase and goes on to activate β1 integrin. In their study, they found that NEO-1 did promote neuroblastoma migration and metastasis ( 36 ). However, some studies suggest that β1 expression is indicative of a better prognosis.…”
Section: Integrins and Neuroblastomamentioning
confidence: 98%
See 1 more Smart Citation
“…NEO-1 is a transmembrane receptor that associates with Focal Adhesion Kinase and goes on to activate β1 integrin. In their study, they found that NEO-1 did promote neuroblastoma migration and metastasis ( 36 ). However, some studies suggest that β1 expression is indicative of a better prognosis.…”
Section: Integrins and Neuroblastomamentioning
confidence: 98%
“…Villanueva et al. suggest that β1 integrin regulation could also be under the control of Neogenin-1 (NEO-1) ( 36 ). NEO-1 is a transmembrane receptor that associates with Focal Adhesion Kinase and goes on to activate β1 integrin.…”
Section: Integrins and Neuroblastomamentioning
confidence: 99%
“…Diğer netrin-1 reseptörü neogeninin nöroblastomda hücre göçü ile de ilgili olduğu belirtilmektedir [96]. Netrin-1-Neogenin-1 sinyal ekseninin, integrin-β1 ve fokal adezyon kinaz aktivasyonu yoluyla nöroblastom hücre göçünü kontrol edebileceği gösterilmiştir [97].…”
Section: Nöroblastomunclassified
“…Whereas the connections of C-MYC with angiogenesis is well stablished, the activation of this transcription factor in response to Netrin-1 signaling remains to be fully characterized ( Figure 2 ). Recent results obtained in our laboratory indicate that interaction between Netrin-1 and NEO1 triggers the activation of Integrin β1 (ITGB1) through the key integrin signaling component Focal Adhesion Kinase (FAK), which promotes cell migration and, consequently, metastasis in neuroblastoma [ 81 ]. Upon Netrin-1 binding to NEO1, FAK undergoes auto-phosphorylation at tyrosine residue 397 to induce intercellular signaling.…”
Section: Signaling Pathways Associated With Netrin-1 and Angiogenesismentioning
confidence: 99%